2021
DOI: 10.3390/healthcare9020175
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Implants, Alternative Prosthetic Rehabilitation in Mandibular Atrophies in Fragile Subjects: A Retrospective Study

Abstract: This study aimed to evaluate the effectiveness of using ultrashort implants in the rehabilitation of jaws of fragile patients. The aim of the study was to retrospectively evaluate the survival rate of full-arch prosthetic rehabilitation on ultrashort implants, length 4 mm, 4 mm in diameter in the premolar and canine area and 4.5 mm in diameter in the molar area, with the insertion torque of 60 Nw and immediate loading. Nineteen patients were evaluated for 3 years clinically and radiographically. The significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Consequently, the periodontal ligament adhesion to the alveolar bone can decrease with mobility or dental exfoliation [2,3]. After dental extraction, the residual alveolar bone crest proceeds to a resorption process, which in some cases cannot permit the implant placement necessary to rehabilitate the created edentulism with a fixed prosthetic device [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the periodontal ligament adhesion to the alveolar bone can decrease with mobility or dental exfoliation [2,3]. After dental extraction, the residual alveolar bone crest proceeds to a resorption process, which in some cases cannot permit the implant placement necessary to rehabilitate the created edentulism with a fixed prosthetic device [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study evaluating the implant success rate of 50 ultra-short dental implants after a follow-up of 8-10 years reported a success rate of 94% and that the ultra-short implants proved to be a reliable solution for prosthetic restoration in patients with severe alveolar bone atrophy 23 . Another study reported that in patients who underwent the rehabilitation of the complete arch using ultrashort implants, the critical rehabilitation issues occur in the first week and after four months following implant placement together with the prosthetic load 22 . The presented a case showed a patient successfully treated with an ultra-short implant of 3 millimeters after the failure and complication of a sinus lift, with a total follow-up of 36 months, confirming the reliability of the ultra-short implant as a valid and effective therapeutic option for severe atrophy bone.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice for the resolution of both partial and total edentulism of patients consists in the use of dental implants (1)(2)(3)(4)(5). In recent decades, their use has exponentially evolved.…”
Section: Introductionmentioning
confidence: 99%